STUDENTS’ PERCEPTION AUTHENTIC ASSESSMENT IN EXPLORING EFL READING CLASS - Nurhasanah, Nurhasanah; Faizah, Maftuhatul; Mistar, Junaidi; Rafiqi, Iqbal (Universitas Al-Amien Prenduan, 2021)
Self-assessment is one of the approaches to evaluate students’ reading skill in English. Through this test, students are permitted to find, know, and increase their reading skill. Reading is a challenging subject for many EFL students. They face various difficulties such as language barriers and lack of exposure to critically analyse the materials. This study aims to identify the students’ responses when they are asked to read in English. Further, a qualitative approach is applied, and data are collected from interview. The result of the study, students gradually respond favourably to the use of authentic assessment. They reveal that authentic assessment (1) motivates them to develop a reading routine so that they can learn more vocabulary and become more comfortable with English discourse, (2) aims to train them to exemplify their reading comprehension in more constructively such as writing reviews, presentations, and discussions, and (3) assists them in evaluating their own reading performance. In conclusion, most students admit that authentic assessment aids them in enjoying reading through a series of social practices, in this case, the use of authentic assessment components such as portfolios, performance assessment, and self-assessment.